Strategic Transformation of Healthcare Personnel Training Planning at Poltekkes Bandung - Heriyanto, Yonan; Adiwisastra, Josy; Broto, Mani Festati; Muhtar, Entang Adhy (Universitas Padjadjaran, 2026)
This research highlights the ineffectiveness of the health human resources (HR) competency development policy at Poltekkes Bandung, which is characterized by a low rate of transfer of learning from training outcomes to the workplace, the absence of a monitoring system leading to skill decay, an imbalance between hard skills and soft skills, and top-down planning that triggers an implementation gap. Using qualitative methods and NVivo 12 analysis on 12 informants, this research reconstructs a demand-driven planning model through an Interprofessional Collaboration (IPC) approach and digitalization. The results formulate an integrated seven-step model, including: synchronizing the curriculum with medical infrastructure, optimizing the Triple Helix partnership, implementing an inclusive IPC curriculum to break down the sectoral (silo-based) work culture, and utilizing the